Gender Participation in Forestry and Agro-Forestry Practices in Sapele Local Government Area of Delta State, Nigeria - Isiorhovoja , R. A. (Asian Journal of Agriculture and Rural Development, 2013)
This study examined the level of gender participation in forestry practices in Sapele Local Government Area of Delta State, Nigeria. Specifically, the study examined the gender distribution of operators among various economic activities in forestry practices and gender differences in income. Data were collected on the marital status, age, educational qualification, number of years of experience in forestry/agroforestry practices, income and challenges encountered from 91 respondents drawn by simple random sampling technique. The data were collected by using copies of a structured questionnaire and were analyzed by using descriptive and inferential statistics. The findings, among others, were that: though there was significant difference in gender distribution by occupation within the subsector, there was no significant gender disparity in gender involvement in terms of number; there was no significant gender difference in the educational qualifications of the operators. Furthermore, that a sizeable proportion of single again women depend on forest resources for their livelihood; that a good proportion of the female in the subsector had no alternative opportunity, finally that there was no significant gender difference in income. We conclude that the forestry economy has high potential for the pursuit of gender equality and for poverty alleviation and recommend that policies and programmes directed towards poverty alleviation in the subsector should, however, be gender sensitive.